An Evaluation Of Liberation Theology in The Light Of Its Praxis - Halim Wiryadinata (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2013)
This article is presented to see how Liberation Theology uses the Scripture wrongly in interpreting their mission. Liberation Theology brings also to the new approach for the third world country. This is how Christian should response Liberation Theology from its praxis.